Industrial cluster as a factor for innovative drive in regions of transformation and structural change: A comparative analysis of East Germany and Poland - Micheal Clarkson; Matthias Fink; Sascha Kraus (Journal for East European Management Studies, 2007)
This article investigates the catalyst effect of industrial cluster formation on innovation propensity using as a basis small and medium enterprises (SMEs) located in two regions of transformation and structural change: Brandenburg in Eastern Germany (the former German Democratic Republic) and Lubuskie in Poland. Based upon Porter's (1990a) Diamond of Competitive Advantage of Regions, which is empirically applied in an explorative manner, this article aims to develop a better understanding of the necessity for interaction between enterprises and policy makers and looks at the rationale of establishing industrial and service clusters as the motor for sustained regional development. – – Der vorliegende Beitrag untersucht den Katalysator-Effekt der Bildung von Industrie-Clustern auf die Innovationsneigung auf Basis einer Befragung kleiner und mittlerer Unternehmen (KMU) aus zwei sich in Transformation und strukturellem Wandel befindlichen Regionen: Brandenburg in Ostdeutschland (frühere Deutsche Demokratische Republik) und Lubuskie in Polen. Vor dem theoretischen Hintergrund von Porters (1990a) Diamanten-Modell der Wettbewerbsvorteile von Regionen, das explorativ empirisch angewendet wird, zeigt dieser Artikel an den empirischen Ergebnissen die Notwendigkeit der Interaktion zwischen Unternehmen und politischen Entscheidungsträgern auf und beleuchtet die Hintergründe der Etablierung von Industrie- und Service- Clustern als Motor für nachhaltige regionale Entwicklung.
Keywords: 650; Cluster; Competitive Advantage; SME; Poland; Eastern Germany